(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
A west-east aligned long cist constructed from sandstone slabs contained teeth and a dozen glass beads. The possibility that the burial demonstrated Anglian influence is considered and in the main discounted.